Going solo the extraordinary rise and surprising appeal of living alone - Klinenberg, Eric 1970- (Penguin Books, 2013)
Renowned sociologist and author Eric Klinenberg explores the dramatic rise of solo living and examines the seismic impact it's having on our culture, business, and politics
Includes bibliographical references (p. [239]-263) and index
Introduction: the singleton society -- Going solo -- The capacity to live alone -- Separating -- Protecting the self -- Together alone -- Aging alone -- Redesigning solo life
Keywords: Living alone / United States; Single people / United States; Single people / United States / Psychology; Alleinstehender; USA